Leg restlessness and hyperparathyroidism in Parkinson's disease, a further clue to RLS pathogenesis? - Marano, Massimo; Pozzilli, Valeria; Magliozzi, Alessandro; Tabacco, Gaia; Naciu, Anda Mihaela; Palermo, Andrea; Di Lazzaro, Vincenzo (Frontiers in Neurology, 2023)
Background: Non-motor manifestations are main features of Parkinson’s disease (PD). These have been associated to Vitamin D abnormalities, but the role of parathormone (PTH) is still obscure. Among the non-motor symptoms of PD, the pathogenesis of restless leg syndrome (RLS) is still debated, but it has been associated to the vitamin D/PTH axis in other disease models. Our study deepens the association between vitamin D and PTH with the prevalence of non-motor symptoms of PD, and explores such relationship in patients reporting leg restlessness. Methods: 50 PD patients were extensively investigated with motor and non-motor scales. Data on serum levels of vitamin D, PTH and related metabolites were obtained, and patients were stratified as having vitamin D deficiency or hyperparathyroidism according to standardized criteria. Results: 80% of PD patients exhibited low vitamin D levels, and hyperparathyroidism was diagnosed in 45%. The analysis of non-motor symptoms profile at the non-motor symptom questionnaire (NMSQ) revealed a 36% of leg restlessness, a main feature of RLS. This was significantly associated with worse motor symptoms, quality of sleep and quality of life. Moreover, it was associated with hyperparathyroidism (OR 3.48) and with PTH levels, independently from vitamin D, calcium/phosphate levels and motor status. Conclusions: Our results suggest a significant association between the vitamin D/PTH axis and leg restlessness in PD. PTH has a putative role in nociceptive modulation and previous evidence on hyperparathyroidism have suggested a possible interrelation with RLS. Further investigations are necessary to add PTH in the non-dopaminergic non-motor landscape of PD.